EFFECT OF LIVELIHOOD DIVERSIFICATION ON RURAL MIGRANTS’ HOUSEHOLD INCOME IN SOUTH-WEST NIGERIA - Ajiboye, A.J.; Ogunniyi, G.; Akinsulu, A.A.; Olarinre, A. A.; Bamisaiye, O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the effect of income diversification on household income among rural migrant households in Southwestern Nigeria. Primary data were collected from 413 respondents selected through a combination of purposive and random sampling techniques across Ekiti, Osun, and Oyo States. Data generated through the administration structured questionnaire which is the main instrument of the study. Descriptive statistics were used to analyze respondents’ socio-economic characteristics, while the Simpson’s Index of Diversification measured the extent of income diversification. The Two-Stage Least Squares (2SLS) regression technique was employed to estimate the impact of income diversification on per capita household income. The results showed that 72.25% of respondents were male, indicating the predominance of male-headed households in rural areas. About 76.75% were first-generation migrants, and approximately 85% had resided in their current locations for at least 15 years, with an average duration of 29.51 years. First-stage regression results identified farm size, farm income, non-farm income, off-farm income, remittance and household asset value at 1% level of significance as strong instruments for income diversification. The study concludes that income diversification and remittance inflows significantly increase per capita household income. On this note, it is thus recommended that rural development policies should adopt a multidimensional approach that enhances access to non-farm and off-farm employment opportunities to improve migrant household welfare.